2018
DOI: 10.2147/ppa.s159293
|View full text |Cite
|
Sign up to set email alerts
|

Predicting medication nonadherence risk in a Chinese inflammatory rheumatic disease population: development and assessment of a new predictive nomogram

Abstract: PurposeThe aim of this study was to develop and internally validate a medication nonadherence risk nomogram in a Chinese population of patients with inflammatory rheumatic diseases.Patients and methodsWe developed a prediction model based on a training dataset of 244 IRD patients, and data were collected from March 2016 to May 2016. Adherence was evaluated using 19-item Compliance Questionnaire Rheumatology. The least absolute shrinkage and selection operator regression model was used to optimize feature selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 37 publications
2
76
0
Order By: Relevance
“…3C . The decision curve revealed that when the threshold probability of a patient and doctor is 20% and 100%, respectively, in the entire cohort, using this nomogram to predict the efficacy of endoscopic nasal septoplasty provide additional benefits as reported previously ( Wang et al, 2018 ). Within this range, net benefit was comparable with several overlaps, on the basis of the prediction nomogram.…”
Section: Resultssupporting
confidence: 63%
“…3C . The decision curve revealed that when the threshold probability of a patient and doctor is 20% and 100%, respectively, in the entire cohort, using this nomogram to predict the efficacy of endoscopic nasal septoplasty provide additional benefits as reported previously ( Wang et al, 2018 ). Within this range, net benefit was comparable with several overlaps, on the basis of the prediction nomogram.…”
Section: Resultssupporting
confidence: 63%
“…The decision curve analysis of the efficacy prediction model of endoscopic NSD surgery is shown in Figure 3C. The decision curve revealed that when the threshold probability of a patient and doctor is 20% and 100%, respectively, in the entire cohort, using this nomogram to predict the efficacy of endoscopic nasal septoplasty provide additional benefits as reported previously (Wang et al, 2018).Within this range, net benefit was comparable with several overlaps, on the basis of the prediction nomogram. Therefore, the decision curve showed that clinical decisions based on the nomogram prediction model yielded better returns.…”
Section: Manuscript To Be Reviewedsupporting
confidence: 56%
“…This method is suitable for high dimensional data compression and can be used to analyse the optimal predicted risk factors of the disease. 22 After features with nonzero coefficients in the LASSO regression model were selected, multivariable logistic regression analysis was performed on patients with DN and DR to screen out all significant risk factors. Multivariable logistic regression analysis was usually used to develop the predicting model 23 Due to the potential connection between DN and DR, to ensure the accuracy of the results, we carried out multivariable logistic regression analysis of the above significant risk factors on the sample data of patients with both DN and DR.…”
Section: Discussionmentioning
confidence: 99%